2021
DOI: 10.3390/microorganisms9040728
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus sp. Strains Inhibit Growth, Adhesion, Biofilm Formation, and Gene Expression of Bacterial Vaginosis-Inducing Gardnerella vaginalis

Abstract: Gardnerella vaginalis contributes significantly to bacterial vaginosis, which causes an ecological imbalance in vaginal microbiota and presents with the depletion of Lactobacillus sp. Lactobacillus supplementation was reported to be an approach to treat bacterial vaginosis. We investigated the applicability of three Lactobacillus sp. strains (Lactobacillus delbrueckii DM8909, Lactiplantibacillus plantarum ATCC14917, and Lactiplantibacillus plantarum ZX27) based on their probiotic abilities in vitro. The three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Coudeyras et al [47] reported the antagonistic activity of L. rhamnosus strain (Lcr35) against vaginal pathogens in cervical cells. Qian et al [48] reported that three Lactobacillus strains (L. delbrueckii DM8909, L. plantarum ATCC14917, and L. plantarum ZX27) inhibited GV growth, adhesion, and biofilm formation in vitro. Similar to the results from previous studies, this study showed that all strains and the mixture adhered well to HeLa cells and exhibited potential antagonistic activity against GV in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Coudeyras et al [47] reported the antagonistic activity of L. rhamnosus strain (Lcr35) against vaginal pathogens in cervical cells. Qian et al [48] reported that three Lactobacillus strains (L. delbrueckii DM8909, L. plantarum ATCC14917, and L. plantarum ZX27) inhibited GV growth, adhesion, and biofilm formation in vitro. Similar to the results from previous studies, this study showed that all strains and the mixture adhered well to HeLa cells and exhibited potential antagonistic activity against GV in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…These three Lactobacillus spp. strains have shown efficacy in the treatment of BV by limiting the growth, adhesion, biofilm formation and virulence properties of G. vaginalis ( Qian et al., 2021 ).…”
Section: Bacterial Vaginosismentioning
confidence: 99%
“…Saunders et al reported that L. reuteri RC-14 and L. rhamnosus GR-1 could reduce G. vaginalis biofilm, suggesting that biosurfactants produced by these lactobacilli might contribute to inhibiting biofilm formation 45 . It was also reported that L. delbrueckii DM8909, Lactiplantibacillus plantarum ATCC14917, and Lactiplantibacillus plantarum ZX27 had antibiofilm abilities against G. vaginalis 46 . It can be concluded that the < 3 kDa LCFSP might have a potency to prevent the formation of G. vaginalis biofilm.…”
Section: Discussionmentioning
confidence: 93%